Formation of allergic pathology in children of Zaporizhzhya Region - T. E. Shumna (Zaporožskij Medicinskij Žurnal)
6275 children (2772 boys and 3503 girls) were questioned, among them 2623 (1158 boys and 1465 girls) habitants of city of Zaporozhуe and 3652 children (1614 boys and 2038 girls) from Zaporozhye region at the age of 6-7 and 13-14 years. It was revealed by factor analysis, that allergic diseases in children of Zaporozhуe region are realized on condition of presence of three basic factors infl uencing on the development of allergic pathology in children, particularly they are environment, medical and biological factors, socio-economic factors.